Research on Key Technologies of OSS Supporting LTE QoS Manangement - Feilong Zhao; Jiangong Zhang (Dianxin kexue)
QoS guarantee is an important component of the LTE network, the OSS must be able to support the operation and management related to the QoS guarantees. This paper analyzes the QoS implementation mechanism in LTE deeply, clarify substance and the relationship among the bearer ID, bearer profile, bearer banding and performance measurement, and points out the basic method of how to achieve end-to-end resource association and performance statistics. The work can provide good reference for the establishment of the OSS that support LTE QoS guarantee.